ANALISIS KETAMPANAN NABI YUSUF DALAM PERSPEKTIF SEMIOTIKA AL-QUR’AN - Akrom, Muhammad (Arabiyat : Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2014)
The topic of this research is the Qur’an semiotics on surah Yusuf. This research collaborates the theory of semiotics and al-Qur’an. This research aims to find out the sense, meaning, and messege of the Qur’an on surah Yusuf. The theories used in this research are theory of meaning component, theory of sense relation, and theory of semiotics. This research is used two approaches. First, heuristic or semantics and second, retroactive or semiotics. DOI: 10.15408/a.v1i2.1141